(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The present comparative study was conducted to investigate the Ardabil people’s use of different types of media (national media, social networks, and satellite channels) to receive news. The present study was conducted using a survey method. It used a researcher-made questionnaire to collect data. The statistical population of the present study included Ardabil’s people, aged over 18 years who used national media, social networks, and satellite channels. The sample size of the study was calculated to be 400 people based on Cochran’s formula. According to the statistical results of the study, most respondents in Ardabil tended to obtain news from social networks, followed by national media, and satellite channels, respectively. The respondents’ level of satisfaction with the content attractiveness of social networks in the indicators of accuracy and transparency, speed of broadcasting the news, neutrality or impartiality of news, using the latest video reports, visual-audio attractiveness, and paying attention to the quality of programs had the highest priority. The majority of the respondents did not have high trust in the news of national media of Iran and believed that the news of national media was less accurate and transparent and the rate of censorship in the news of national media was higher than that in social networks and satellite channels. Respondents believed that national media used fewer new video reports compared to social networks and satellite channels. Content attractiveness, including paying attention to the quality of programs in the news of national media, was at a lower level than that in social networks and satellite channelsreading habit. In addition, it is thought that it would be beneficial to provide teachers with in-service training for the exam.